O Modelo policial e as políticas institucionais no controle da violência e da criminalidade: um estudo na Polícia Civil do Pará - BEZERRA, Thais Maia Carvalho (Universidade Federal do Pará, 2013)
According to the Brazilian Federal Constitution of 1988, public safety is the State's duty, right and responsibility of all. It is practiced in several levels of responsibilities by police institutions and other organizations. The main objectives are maintaining the public order and people and properties safety as well as ensuring the fulfillment of the democratic State of law. On the state level, the Civil Police is one of the organs responsible for ensuring the society protection, having an organizational structure and a management focused on performing its institutional mission. Given this scenario of information and research lacks about the institutions in the state of Pará, in special those related to public safety, this study investigates the policing model adopted in the Civil Police of Pará regarding the organizational structure and the management of the organ as well as institutional policies accomplished with the purpose to control the violence and crime in the State. As result it is observed that the Civil Police of Para is organized structurally on direction, advisory and and others departments which reinforcing the exercise of police activity. Its highest individual representation is the General Delegate of the Civil Police. Regarding the management of the institution, this work suggests that the centralization and bureaucratization are presented in the execution of their activities. Moreover, institutional policies, such as the Revolving Fund and the Policy Integrationist, contribute to an evolution in relation to managerial decentralization of activities. Here it is demonstrated that the organizational structure and management as well as institutional policies can influence the development of police work. It is important to highlight that these variables are the main bases for the implementation of the main police activity: the protection of human dignity. This work is characterized as inedited and pioneering, and may serve as support for implementation of public policy more assertive and adjusted to the society requirements.